2016
DOI: 10.3389/fpls.2016.01606
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Functional Analysis of Two Petunia PhEILs

Abstract: Ethylene plays an important role in flower senescence of many plants. Arabidopsis ETHYLENE INSENSITIVE3 (EIN3) and its homolog EIL1 are the downstream component of ethylene signaling transduction. However, the function of EILs during flower senescence remains unknown. Here, a petunia EIL gene, PhEIL2, was isolated. Phylogenetic tree showed that PhEIL1, whose coding gene is previously isolated, and PhEIL2 are the homologs of Arabidopsis AtEIL3 and AtEIL1, respectively. The expression of both PhEIL1 and PhEIL2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In cut carnation, silver nanoparticles treatment delayed petal senescence, decreased ethylene synthesis, and the expression levels of EIL1/2, a homolog of EIN3 , were significantly downregulated in the silver nanoparticles treatment compared with control flowers [ 44 ]. The expression of PhEIL1/2 increased during corolla senescence and VIGS mediated PhEIL1/2 silencing delayed flower senescence and reduced ethylene production [ 45 ]. During flower senescence of C. lutchuensis , EIN3 genes upregulated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In cut carnation, silver nanoparticles treatment delayed petal senescence, decreased ethylene synthesis, and the expression levels of EIL1/2, a homolog of EIN3 , were significantly downregulated in the silver nanoparticles treatment compared with control flowers [ 44 ]. The expression of PhEIL1/2 increased during corolla senescence and VIGS mediated PhEIL1/2 silencing delayed flower senescence and reduced ethylene production [ 45 ]. During flower senescence of C. lutchuensis , EIN3 genes upregulated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that ethylene treatment promote ethylene autocatalysis and accelerated flower senescence in petunia and carnation [ 65 ]. In addition, ethylene treatment changed the expression of genes inveolved in ethylene biosynthesis and signalling transduction [ 28 , 66 ]. In this study, the results of both transcriptome and PCR assay showed that ethylene treatment increased the number of AS precursor RNAs of most genes involved in ethylene biosynthesis and signalling transduction in petunia corollas, which could provide a new perspective of regulation of ethylene on flower senescence in petunia.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the flowering plants show a decrease in floral lifetime due to increased ethylene production [ 131 ]. Previously, Liu et al [ 132 ] used virus-induced silencing to silence suspected ethylene signaling components EIL1 and EIL2 in petunia. They also observed that the EIL genes are functionally redundant and that down regulating the two genes affects floral bloom lifespan.…”
Section: Applications Of Crispr/cas9 System In Floriculturementioning
confidence: 99%
“…They also observed that the EIL genes are functionally redundant and that down regulating the two genes affects floral bloom lifespan. However, EIL gene silencing resulted in no phenotypic changes in transgenic plants other than increased flower longevity, demonstrating that EIL genes have a specific function [ 132 , 133 ]. Flower lifetime can be increased by reducing ethylene production, which can be reduced by targeting a critical enzyme in the ethylene metabolism [ 1-aminocyclopropane-1-carboxylate oxidase ( ACO )] [ 134 , 135 ].…”
Section: Applications Of Crispr/cas9 System In Floriculturementioning
confidence: 99%